ANALISIS PROSEDUR EMBARKASI DAN DISEMBARKASI DALAM MENJAMIN KESELAMATAN PENUMPANG KM SINABUNG - Anjabi, Muhammad; Dion Lebang; Yohanis Kosso Tedang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The embarkation and disembarkation processes on KM Sinabung encounter multiple safety challenges including overcrowding, slippery gangways, and excessive passenger baggage. This study aims to analyze the implementation of safety procedures to minimize maritime accident risks during these processes. A descriptive qualitative approach was employed, using direct observations, in-depth interviews with deck officers and crew, and document analysis of regulatory standards and company SOPs. Data were analyzed inductively through reduction, organization, and conclusion drawing. Results indicate suboptimal procedural implementation caused by passenger indiscipline, limited supervision during peak hours, and environmental factors such as adverse weather and port infrastructure limitations. Mitigation strategies included entrance sterilization, CCTV optimization, clear passenger guidance, coordination with port authorities, and crew training for crowd management. The findings emphasize the need for strict enforcement of baggage regulations, improved crew oversight, and adherence to international and national maritime safety standards to ensure passenger safety and operational efficiency on KM Sinabung.